A study on prevalence of hypertension and its relationship with overweight and obesity in adolescents and young adults, Nizamabad city - Raj, G. Chethan; Junapudi, Syam Sundar (International Journal Of Community Medicine And Public Health, 2019)
Background: The overall imbalance between unhealthy diet intake and physical activity leads to obesity which contributes to high blood pressure and high cholesterol. It is multi factorial disease and changes in the levels of blood pressure and blood lipids differ by age sex and race and are influenced by body fat and dietary patterns. These risk factors need to be monitored and evaluated in childhood and adolescents. So identifying and modifying the risk factors in early age reduces the incidence in adolescents and adult. Prevalence of hypertension varies across countries and states. The prevalence of hypertension in India is reported as ranging from 10 to 30.9%. The objective of the present study is to observe the prevalence hypertension among study population and to study contributing factors for hypertension among study population. Methods: A cross sectional study done on 100 adolescents and young adults of both sexes in the age group 17 to 25 years from 2 degree colleges randomly selected in Nizamabad city, Telangana, India. Results: In the present study population 52 were males and 48 were females, 22 students belongs to rural area and 78 belongs to urban area, pre-hypertension and hypertension was found 8% in both age groups. Overweight and obesity (>25) was found 7% in 17-19 age group and 9% in 20-25 age group. Pre-hypertension and hypertension was found among 10% of alcoholics. Conclusions: The result of our study concluded that there is increasing prevalence of hypertension with increase in age and is associated with overweight and obesity.